REPRESENTATION OF ARRANGE MARRIAGES IN SONIAH KAMAL UNMARRIAGEABLE PRIDE AND PREJUDICE - Nabeela Gul; Bilara Uzair; Faiza yousaf; Attiya fayaz; Yasina Tabasum (International Journal of Contemporary Issues in Social Sciences, 2024)
This research work has examined and explored the representation of arranged marriages of women in Soniah Kamal, novel Unmarriageable by using the theoretical framework of Kate Millet’s radical feminism. This theoretical framework sees that the patriarchal culture is fundamentally responsible for the oppression of women in Pakistani society. The present study by employing the text analysis method has explored that women in Pakistani society are marginalized and oppressed as they are forced for early marriages. This deprives them of the basic right of education.The protagonist sister Jane, suffers from the woes of early marriages which resists her social, mental and educational development. Alys the protagonist remains pragmatic while observing her sister woes after her marriage. Early marriages resist social mobility of women. Soniah retells the story of Pride and Prejudice by Jane Austen by giving voice to the hopes, frustration and fears of women. Females are deeply marginalized by the patriarchal social system and are torn between mental disorder and traditional norms. Their endeavor to challenge social laws and get rid of the conventional rules of Pakistani society proves self-destructive. Gender inequality, lack of educational rights, political and domestic oppression is the root causes of women woes in the current social context. Early marriages disrupt their education and damage their dreams, social mobility and security. Resultantly, Alys tries to disengage herself from early marriage and in turn, resort to completion of her education towards successful life. The implication is that early marriages are hindrance to women development in society.